SEDIMENT CHARACTERISTICS AND DISTRIBUTION OF CRAB Scopimera globosa ON THE SELAT BARU BEACH BENGKALIS DISTRICT - Rahdian Putra; Elizal '; Thamrin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted in December 2016 at the Selat Baru Beach of Bengkalis District, Riau Province. The aim of the research is to find out and to analyze, the characteristics of sediment and the distribution of crab Scopimera globosa, as the influence of sediment grain size on the abundance of crabs. This method used was survey method and the sampling location determined by purposive sampling. The location were divided into three stations and at each station there were three sub-stations spread in the intertidal zone and split three sub-zones to : upper, middle and lower. The type of sediment on this beach consisted of sand fraction and dominated by fine sand, with the distribution of the fraction from Well sorted, Moderately well sorted, Poorly sorted and Very poorly sorted. The distribution of crabs Scopimera globosa was a clumped pattern on each station with the highest abundance value in second station located and the middle sub-zone (the most productive zone for growth of the crab Scopimera globosa) and the sediment mean size to contributes 1.2% in control to distribution of the crab Scopimera globosa.Key words : Sediment Characteristics, Distribution Scopimera globosa, sand fraction, Sub-Zone Middle, Contribution of 1.2%.